Perfil bioquímico, inclusive proteinograma, do soro lácteo de búfalas primíparas e pluríparas sadias ao longo da lactação - Pizauro, Lucas J.L. [UNESP]; da Silva, Daniela G. [UNESP]; Santana, André M. [UNESP]; Morais, Stella M.A. [UNESP]; Benincasa, Natália C. [UNESP]; Fagliari, José J. [UNESP] (FapUNIFESP (SciELO), 2014)
To evaluate the biochemical profile and protein concentration of whey from milk samples of healthy Murrah primiparous and pluriparous buffaloes, 30 female buffaloes were analyzed during a complete lactation. The animals were divided into three groups: G1 = 10 primiparous buffaloes, G2 = 10 pluriparous buffaloes with 2-3 lactations and G3 = 10 pluriparous buffaloes with > 3 lactations. The lactation period was divided into: early stage (I: 1-3 months of lactation), intermediate stage (T: 4-6 months of lactation) and final stage (F: 7-9 months of lactation). Before milk sampling, physical examination of the mammary gland, strip cup test and California Mastitis Test (CMT) were performed. After mammary quarters asepsis, 20mL of milk were collected monthly from each mammary quarter, during a complete lactation, in sterilized plastic bottles without preservative, in order to perform microbiological isolation, biochemical profile and protein electrophoresis in sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and 30mL of milk from each mammary quarter were collect, in sterilized plastic bottles containing preservative bronopol to perform the somatic cell count (SCC). A total of 1,042 milk samples were collected from the experimental groups during lactation, of which 923 samples showed negative reaction to CMT and negative microbiological isolation and were selected to biochemical profile analysis and protein electrophoresis in SDS-PAGE. There were influence of parity order and stage of lactation in biochemical profile and protein concentration of healthy Murrah buffaloes' whey. Primiparous buffaloes (G1) showed higher gamma-glutamyltransferase (GGT: 2,346 U/L), alkaline phosphatase (ALP: 181 U/L), phosphorus (P; 56.6mg/dL), potassium (K; 32.0mg/dL) and a-lactalbumin (458mg/dL). Buffaloes with 2-3 lactations (G2) showed higher SCC (70,700 cells/mL) and higher concentrations of total protein (1.55g/dL), albumin (100mg/dL), magnesium (Mg; 8.80mg/dL), chlorides (Cl; 176mg/dL), iron (Fe; 10.7µg/dL), sodium (Na; 178mMol/L) and lactoferrin (59.5mg/ dL). Bufalloes with > 3 lactations (G3) showed higher concentrations of total calcium (Ca; 41.8mg/dL), ionized calcium (iCa; 2.92mMol/L), immunoglobulin A (IgA; 1.32mg/dL), serum albumin (99.1mg/dL), immunoglobulin G (IgG; 49.7mg/dL) and ß-lactoglobulin (1,068mg/dL). During lactation it was observed increase in SCC, GGT, ALP, total protein, albumin, P, Mg, Cl, Na, lactoferrin, serum albumin, IgG and a-lactalbumin, as well as decrease in concentrations of Ca, Fe, iCa, K, IgA and ß-lactoglobulin in buffaloes' whey. The results may be used as reference for buffaloes and to support diagnosis and prognosis of diseases common to lactation periods.
Biochemical profile, including protein concentration, of whey from healthy primiparous and pluriparous buffaloes during lactation